PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. GREENLY LIFESTYLE INDONESIA AREA JAKARTA - Evianti, Eni; Ariyanto, Aris (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of leadership style and work discipline on employee performance at PT Greenly Lifestyle Indonesia Jakarta Area. The research method used is the primary data quantitative research method. Research location Jln Taman Daan Mogot Raya no. 4, RT 02 RW 01, Jl. North Duren, Grogol Petamburan District, West Jakarta City. The population of this research is employees at PT Greenly Lifestyle Indonesia Jakarta Area. The sample for this research was 97 respondents, the sampling technique was using the Solvin technique. The data collection methods used were questionnaires, literature study and observation. The data analysis method uses validity tests, reliability tests, classical assumption tests, linear regression analysis, coefficient of determination tests, T tests and F tests with the help of SPSS version 26 software. The results of the research show that the t test can determine the Leadership Style variable having a simple linear regression Y = 7,007 + 0.812 So it can be concluded that the Leadership Style variable influences employee performance. The Discipline variable has a simple linear regression equation Y = 4,560 + 0.853 < table 1.661. So it can be concluded that the Work Discipline variable influences employee performance. The research results of the F test for the Leadership Style and Work Discipline variables have a simple linear regression equation Y = 2,892 + 0.252 X1 + 0.659 ftable (211,058 > 3,090) and the significance value is smaller than 5% (0.000 < 0.05). This means that together the independent variables consisting of the Leadership Style and Work Discipline variables have an effect on employee performance.